Disease Resolution in Chikungunya—What Decides the Outcome? - Srivastava, Priyanshu; Kumar, Ankit; Hasan, Abdul; Mehta, Divya; Kumar, Ramesh; Sharma, Chetan; Sunil, Sujatha (Frontiers in Immunology, 2020)
Abstract: Chikungunya disease (CHIKD) is a viral infection caused by an alphavirus, chikungunya virus (CHIKV) and triggers epidemics in form of large outbreaks. Despite the low mortality rate, it is a major public health concern owing to high morbidity in affected individuals. The complete spectrum of this disease can be divided into four phases based on its clinical presentation and immunopathology. When a susceptible individual is bitten by an infected mosquito, the bite triggers inflammatory responses attracting neutrophils and initiating a cascade of events resulting in the entry of the virus into permissive cells and is termed as the pre-acute or the intrinsic incubation phase. The virus utilizes the cellular components of the innate immune system to enter the circulation and reaches primary sites of infection like a lymph node, spleen, and liver. Also, at this point, antigen-presenting cells (APCs) presents the viral antigens to the T cells thereby activating and initiating adaptive immune responses. This phase is marked by the exhibition of clinical symptoms such as fever, rashes, arthralgia, myalgia and is termed as the acute phase of the disease. Viremia reaches its peak during this phase thereby enhancing the antigen-specific host immune response. Simultaneously, T cell mediated activation of B cells leads to the formation of CHIKV specific antibodies. Increase in titres of neutralizing IgG/IgM antibodies results in the clearance of virus from the bloodstream and marks the initiation of the post-acute phase. Immune responses mounted during this phase of the infection determine the degree of disease progression or its resolution. Some patients may progress to a chronic arthritic phase of the disease that may last from a few months to several years owing to compromised disease resolution. The present review discusses the immunopathology of CHIKD and the factors that dictate disease progression and its resolution.